Degradable medical 3D printing magnesium alloy cardiovascular stent and preparation method thereof
By introducing enhanced phase and 3D printing technology into magnesium alloy cardiovascular stents, the problem of insufficient mechanical properties and corrosion resistance of magnesium alloy stents is solved, and efficient vascular regeneration and reduced production costs are achieved.
Patent Information
- Application Number
- CN202411803354.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-12-10
AI Technical Summary
Existing cardiovascular stent materials such as stainless steel and titanium alloys may cause vascular endothelial hyperplasia after long-term implantation, leading to restenosis. The yield and tensile strength of magnesium alloy cardiovascular stents are low and the corrosion resistance is poor.
Using a degradable medical 3D printed magnesium alloy cardiovascular stent, the yield strength and tensile strength of magnesium alloy are improved by introducing strengthening phases Zn2Zr, MgZn2, Mg3YZn6, combined with 3D printing technology, and reducing the yield strength and tensile strength of magnesium alloy through tilt smelting and atomization powder making process. Impurity content, improves the purity and corrosion resistance of the material.
It significantly improves the mechanical properties and corrosion resistance of magnesium alloy cardiovascular stents, extends the degradation time of the stent, promotes blood vessel healing and regeneration, avoids secondary surgery and reduces production costs.
Smart Images

Figure CN119280470A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of human body implantable medical devices, and in particular to a degradable medical 3D printed magnesium alloy cardiovascular stent and a preparation method thereof. Background Art
[0002] Cardiovascular stents are mainly used to treat cardiovascular diseases such as coronary heart disease, peripheral vascular disease and cerebrovascular disease. By implanting the stent into the diseased blood vessel, the blood vessel wall is supported to prevent the blood vessel from collapsing, thereby restoring blood flow and relieving the patient's symptoms.
[0003] At present, the stent materials used in the treatment of cardiovascular diseases are mainly stainless steel and titanium alloys. Although these materials have high strength, they may cause vascular intimal hyperplasia and lead to restenosis after long-term implantation.
[0004] The present invention provides a degradable medical 3D printed magnesium alloy cardiovascular stent and a preparation method thereof, which improves the yield strength, tensile strength and corrosion resistance of the magnesium alloy cardiovascular stent, thereby improving the stability of the magnesium alloy cardiovascular stent, and solves the technical problems of low yield strength and tensile strength and poor corrosion resistance of the magnesium alloy cardiovascular stent in the prior art. Summary of the invention
[0005] The present invention provides a degradable medical 3D printed magnesium alloy cardiovascular stent and a preparation method thereof, which are used to solve the technical problems of low yield strength and tensile strength and poor corrosion resistance of magnesium alloy cardiovascular stents in the prior art.
[0006] In one aspect, the present invention provides a degradable medical 3D printed magnesium alloy cardiovascular stent, wherein the magnesium alloy cardiovascular stent is composed of the following components in percentage by mass: Zinc 2.0~3.0wt%; Calcium 0.9~1.0wt%; Yttrium 0.3~0.4wt%; Zirconium 0.2~0.3wt%; The balance is magnesium and unavoidable impurities.
[0007] According to a degradable medical 3D printed magnesium alloy cardiovascular stent provided by the present invention, the unavoidable impurities are composed of the following components in mass percentage: Iron ≤ 0.08wt%; Copper ≤ 0.005wt%; Nickel ≤ 0.002wt%.
[0008] On the other hand, the present invention also provides a method for preparing a degradable medical 3D printed magnesium alloy cardiovascular stent, comprising the following steps: (1) According to the elemental composition of the degradable medical 3D printed magnesium alloy cardiovascular stent, weigh the magnesium ingot, zinc block, Mg-30Ca master alloy, Mg-30Y master alloy and Mg-30Zr master alloy; (2) heating the smelting equipment, and smelting the magnesium ingot, zinc block, Mg-30Ca master alloy, Mg-30Y master alloy and Mg-30Zr master alloy under a protective atmosphere, and obtaining a magnesium alloy melt after heat preservation treatment; (3) Preheating the mold, pouring the magnesium alloy melt into the preheated mold under a protective atmosphere, and cooling to obtain an ingot; (4) remelting the ingot, keeping it warm, pouring it into a preheated mold, and cooling it to obtain a magnesium alloy base material; (5) melting the magnesium alloy base material to obtain a magnesium alloy melt; (6) Raising the temperature to superheat the melt, transferring it to a gas atomization device, cooling it into solid powder particles, and sieving it to obtain magnesium alloy powder; (7) The magnesium alloy powder is 3D printed to obtain a biodegradable medical 3D printed magnesium alloy cardiovascular stent.
[0009] According to a method for preparing a degradable medical 3D printed magnesium alloy cardiovascular stent provided by the present invention, the protective atmosphere is argon gas.
[0010] According to a method for preparing a degradable medical 3D printed magnesium alloy cardiovascular stent provided by the present invention, in the step (2), the melting equipment is heated to 720-750° C., and the heat preservation time is 10 minutes.
[0011] According to a method for preparing a degradable medical 3D printed magnesium alloy cardiovascular stent provided by the present invention, in the step (3), the mold is preheated to 200-250° C. and the cooling time is 20-40 minutes.
[0012] According to the method for preparing a degradable medical 3D printed magnesium alloy cardiovascular stent provided by the present invention, in the step (4), the melting temperature is 720-750° C. and the insulation time is 10 minutes.
[0013] According to the method for preparing a degradable medical 3D printed magnesium alloy cardiovascular stent provided by the present invention, in the step (4), the mold is preheated to 200-250° C. and the cooling time is 20-40 minutes. According to a method for preparing a degradable medical 3D printed magnesium alloy cardiovascular stent provided by the present invention, in step (5), the vacuum degree in the furnace during smelting is 10 -2 ~10 -3 MPa, the smelting temperature is 680~720℃, and the smelting time is 20~30 minutes.
[0014] According to the method for preparing a degradable medical 3D printed magnesium alloy cardiovascular stent provided by the present invention, in the step (6), the melt is overheated to 50-100°C, the high-speed gas in the atomization device is argon, and the gas flow rate is 2-4 m / s. 3 / h, and the particle size distribution after screening is 10~150 mesh.
[0015] According to a method for preparing a degradable medical 3D printed magnesium alloy cardiovascular stent provided by the present invention, in step (7), the process parameters of 3D printing are: laser power 200~400W, scanning speed 600~1000mm / s, and scanning layer thickness 0.1mm.
[0016] The present invention provides a degradable medical 3D printed magnesium alloy cardiovascular stent and a preparation method thereof. By introducing strengthening phases Zn2Zr, MgZn2, and Mg3YZn6, dislocation movement and grain boundary sliding are effectively hindered, the yield strength and tensile strength of the magnesium alloy are improved, and the technical problem of poor mechanical properties of magnesium alloy cardiovascular stents in the prior art is solved, and the beneficial effect of improving the mechanical properties of magnesium alloy cardiovascular stents is achieved. The present invention combines medical magnesium alloys with 3D printing technology to reduce material defects and heterogeneity, improve the mechanical properties and corrosion resistance of magnesium alloy cardiovascular stents, solve the technical problems of poor mechanical properties and poor corrosion resistance of magnesium alloy cardiovascular stents in the prior art, and achieve the beneficial effects of accurately customizing the shape and size of the stent according to the individual needs of the patient, short production cycle, and low cost. A degradable medical 3D printed magnesium alloy cardiovascular stent provided by the present invention can be gradually degraded and absorbed in the body, which solves the technical problem that stainless steel and titanium alloy cardiovascular stents in the prior art need to be removed by subsequent surgery, and achieves the beneficial effect of avoiding secondary surgery to remove the stent, and the products in the degradation process (such as magnesium hydroxide, etc.) promote the growth of vascular endothelial cells, which is helpful for vascular regeneration and healing. In the process of tilting smelting, the present invention can effectively remove oxides and impurities emerging on the surface of the melt through tilting operation, thereby improving the purity of the alloy and achieving the beneficial effect of improving the mechanical properties and corrosion resistance of the magnesium alloy. The present invention provides a preparation method of a degradable medical 3D printed magnesium alloy cardiovascular stent, which is obtained by two tilting smeltings and finally atomizing powder making, and the obtained powder particles have uniform distribution of components and low impurity content, which is conducive to 3D printing. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0018] Figure 1 is a metallographic image of the degradable medical 3D printed magnesium alloy cardiovascular stent according to Example 1 of the present invention; Figure 2 This is a corrosion morphology diagram of the degradable medical 3D printed magnesium alloy cardiovascular stent according to Example 1 of the present invention; Figure 3 is an EIS impedance curve diagram of Example 1 of the present invention and Comparative Example 1 after being immersed in SBF simulated body fluid for 168 hours; Figure 4 It is a polarization curve diagram of Example 1 of the present invention and Comparative Example 1 after being immersed in SBF simulated body fluid for 1 hour. DETAILED DESCRIPTION
[0019] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with the drawings of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0020] Combine the following Figure 1-Figure 4 Description of the invention Figure 1 This is a metallographic image of the degradable medical 3D printed magnesium alloy cardiovascular stent according to Example 1 of the present invention.
[0021] like Figure 1 As shown in the figure, the rapid cooling characteristics of 3D printing enable the magnesium alloy to form uniform and fine precipitates during the solidification process. On the one hand, the fine and uniform precipitates can effectively hinder the slip of dislocations, thereby producing precipitation strengthening, significantly improving the yield strength and tensile strength of the magnesium alloy; on the other hand, the uniform distribution of the precipitates helps to form a denser and more uniform oxide film on the surface of the magnesium alloy, which can effectively isolate the contact between the metal matrix and the corrosive medium, thereby enhancing the corrosion resistance of the magnesium alloy.
[0022] Figure 2 This is a corrosion morphology diagram of the degradable medical 3D printed magnesium alloy cardiovascular stent according to Example 1 of the present invention.
[0023] like Figure 2As shown, a dense and uniform protective layer is formed on the surface of Example 1 of the present invention after being immersed in SBF simulated body fluid for 48 hours. Through a specific alloy element ratio, the uniform distribution of the precipitated phase can be promoted, thereby improving the density and protection of the film layer. At the same time, the rapid prototyping and cooling characteristics of 3D printing technology enable the material to form a fine and uniform microstructure during the solidification process, thereby improving the integrity of the protective layer. This dense protective layer effectively prevents the penetration of corrosive media and significantly prolongs the degradation time of magnesium alloys. Therefore, through the synergistic effect of a specific element ratio and the 3D printing process, the corrosion resistance of the magnesium alloy is significantly enhanced.
[0024] Figure 3 It is an EIS impedance curve diagram of Example 1 of the present invention and Comparative Example 1 after being immersed in SBF simulated body fluid for 168 hours.
[0025] like Figure 3 As shown, after Example 1 and Comparative Example 1 of the present invention were immersed in SBF simulated body fluid for 168 hours, both Example 1 and Comparative Example 1 had inductive arcs after immersion for 168 hours, but the diameter of the capacitive arc of Example 1 was much larger than that of Comparative Example 1. Generally speaking, the diameter of the capacitive arc is proportional to the corrosion resistance of the alloy, while the appearance of the inductive arc is related to the initiation and instability expansion of local corrosion. It can be seen that local corrosion occurred on the surfaces of both alloys in Example 1 and Comparative Example 1, but Example 1 had better corrosion resistance.
[0026] Figure 4 It is a polarization curve diagram of Example 1 of the present invention and Comparative Example 1 after being immersed in SBF simulated body fluid for 1 hour.
[0027] like Figure 4 As shown, after Example 1 and Comparative Example 1 of the present invention were immersed in SBF simulated body fluid for 1 hour, it was observed that the anode branch of the polarization curve of Example 1 showed obvious film rupture potential (blue circle area), while the polarization curve of Comparative Example 1 did not have this feature. This indicates that at the initial stage of immersion, a dense protective product film will be formed on the surface of Example 1, while local corrosion has occurred in Comparative Example 1 at the initial stage of immersion.
[0028] The present invention provides a degradable medical 3D printed magnesium alloy cardiovascular stent, which is composed of the following components in percentage by mass: 2.0-3.0wt% zinc, 0.9-1.0wt% calcium, 0.3-0.4wt% yttrium, 0.2-0.3wt% zirconium, and the balance being magnesium and inevitable impurities; preferably 2.2-2.8wt% zinc, 0.92-0.98wt% calcium, 0.32-0.38wt% yttrium, and 0.22-0.28wt% zirconium; further preferably 2.4-2.6wt% zinc, 0.94-0.96wt% calcium, 0.33-0.36wt% yttrium, and 0.24-0.26wt% zirconium.
[0029] According to a degradable medical 3D printed magnesium alloy cardiovascular stent provided by the present invention, the unavoidable impurities consist of the following components in percentage by mass: iron ≤ 0.08wt%, copper ≤ 0.005wt%, and nickel ≤ 0.002wt%.
[0030] On the other hand, the present invention also provides a method for preparing a degradable medical 3D printed magnesium alloy cardiovascular stent, comprising the following steps: (1) According to the elemental composition of the degradable medical 3D printed magnesium alloy cardiovascular stent, weigh the magnesium ingot, zinc block, Mg-30Ca master alloy, Mg-30Y master alloy and Mg-30Zr master alloy; (2) heating the smelting equipment, and smelting the magnesium ingot, zinc block, Mg-30Ca master alloy, Mg-30Y master alloy and Mg-30Zr master alloy under a protective atmosphere, and obtaining a magnesium alloy melt after heat preservation treatment; (3) Preheating the mold, pouring the magnesium alloy melt into the preheated mold under a protective atmosphere, and cooling to obtain an ingot; (4) remelting the ingot, keeping it warm, pouring it into a preheated mold, and cooling it to obtain a magnesium alloy base material; (5) melting the magnesium alloy base material to obtain a magnesium alloy melt; (6) Raising the temperature to superheat the melt, transferring it to a gas atomization device, cooling it into solid powder particles, and sieving it to obtain magnesium alloy powder; (7) The magnesium alloy powder is 3D printed to obtain a biodegradable medical 3D printed magnesium alloy cardiovascular stent.
[0031] According to a method for preparing a degradable medical 3D printed magnesium alloy cardiovascular stent provided by the present invention, the protective atmosphere is argon gas.
[0032] According to a method for preparing a degradable medical 3D printed magnesium alloy cardiovascular stent provided by the present invention, in the step (2), the melting equipment is heated to 720-750° C., preferably 725-745° C., and more preferably 730-740° C.; the heat preservation treatment time is 10 minutes.
[0033] According to a method for preparing a degradable medical 3D printed magnesium alloy cardiovascular stent provided by the present invention, in the step (3), the mold is preheated to 200-250° C., preferably 210-240° C., and more preferably 220-230° C.; the cooling time is 20-40 minutes, preferably 24-36 minutes, and more preferably 28-32 minutes.
[0034] According to a method for preparing a degradable medical 3D printed magnesium alloy cardiovascular stent provided by the present invention, in the step (4), the melting temperature is 720-750° C., preferably 725-745° C., and more preferably 730-740° C.; and the holding time is 10 minutes.
[0035] According to a method for preparing a degradable medical 3D printed magnesium alloy cardiovascular stent provided by the present invention, in the step (4), the mold is preheated to 200-250° C., preferably 210-240° C., and more preferably 220-230° C.; the cooling time is 20-40 minutes, preferably 24-36 minutes, and more preferably 28-32 minutes.
[0036] According to a method for preparing a degradable medical 3D printed magnesium alloy cardiovascular stent provided by the present invention, in step (5), the vacuum degree in the furnace during smelting is 10 -2 ~10 -3 MPa, the smelting temperature is 680-720°C, preferably 690-710°C, and more preferably 695-705°C; the smelting time is 20-30 minutes, preferably 22-28 minutes, and more preferably 24-26 minutes.
[0037] According to a method for preparing a degradable medical 3D printed magnesium alloy cardiovascular stent provided by the present invention, in the step (6), the melt is overheated to 50-100°C, preferably 60-90°C, and more preferably 70-80°C; the high-speed gas in the atomization device is argon gas, and the gas flow rate is 2-4 m 3 / h, and the particle size distribution after screening is 10~150 mesh.
[0038] According to a method for preparing a degradable medical 3D printed magnesium alloy cardiovascular stent provided by the present invention, in the step (7), the process parameters of 3D printing are: laser power 200~400W, preferably 220~380W, more preferably 240~340W; scanning speed 600~1000mm / s, preferably 700~900mm / s, more preferably 750~850mm / s; scanning layer thickness 0.1mm.
[0039] Example 1 Weigh 867 g magnesium ingot, 25 g zinc block, 105 g Mg-30Ca master alloy, 18 g Mg-30Y master alloy and 30 g Mg-30Zr master alloy. The weight percentage burnout rate of each element during the smelting process is Mg 5%, Zn 6%, Ca70%, Y 35%, Zr 70%. Heat the tilting smelting equipment to 730°C, and melt the weighed magnesium ingot, zinc block, Mg-30Ca master alloy, Mg-30Y master alloy and Mg-30Zr master alloy in an argon atmosphere. After heat preservation for 10 minutes, a magnesium alloy melt is obtained. Preheat the mold to 250°C, and in an argon atmosphere, tilt the tilting smelting equipment 80° to cast the magnesium alloy melt into the preheated mold, and air cool for 30 minutes to obtain an ingot. The ingot was placed in the tilting melting equipment again, and the tilting melting equipment was heated to 730°C. The ingot was melted again in an argon atmosphere. After heat preservation for 10 minutes, it was poured into a mold preheated to 250°C and air-cooled for 30 minutes to obtain a magnesium alloy matrix. The magnesium alloy matrix was placed in a melting furnace, and the vacuum degree in the melting furnace was set to 5×10 -3 MPa, set the temperature in the melting furnace to 720℃, melt for 30 minutes, and obtain magnesium alloy melt. Raise the temperature and superheat the melt by 50℃. When the magnesium alloy melt reaches the superheat temperature, pour it into the nozzle of the gas atomization device and use a gas flow rate of 2.5 m 3 / h argon gas flow impacts the molten metal, causing the magnesium alloy melt to be quickly atomized into droplets, and then quickly cooled into solid powder particles. After sieving, magnesium alloy powder with a particle size of 10-150 mesh was obtained. The laser power of the 3D printer was set to 250W, the scanning speed was 800mm / s, and the scanning thickness was 0.1mm. The magnesium alloy powder was 3D printed to obtain a degradable medical 3D printed magnesium alloy cardiovascular stent.
[0040] After testing, the degradable medical 3D printed magnesium alloy cardiovascular stent of the present embodiment is composed of the following components in mass percentage: Zn 2.48wt%, Ca 0.94wt%, Y 0.33wt%, Zr 0.26wt%, impurity elements Fe≤0.08wt%, Cu≤0.005wt%, Ni≤0.002wt%, and the balance is magnesium; the degradable medical 3D printed magnesium alloy cardiovascular stent obtained in the present embodiment was subjected to a 7-day SBF simulated body fluid immersion test, and the corrosion rate was 1.05 mm / year; the degradable medical 3D printed magnesium alloy cardiovascular stent obtained in the present embodiment was subjected to a tensile test, and the yield strength was 146.7 MPa and the tensile strength was 242.1 MPa.
[0041] Example 2 Weigh 875 g of magnesium ingot, 25 g of zinc block, 100 g of Mg-30Ca master alloy, 20 g of Mg-30Y master alloy and 25 g of Mg-30Zr master alloy. The weight percentage burnout rate of each element during the smelting process is Mg 5%, Zn 6%, Ca70%, Y 35%, and Zr 70%. Heat the tilting smelting equipment to 740°C, and melt the weighed magnesium ingot, zinc block, Mg-30Ca master alloy, Mg-30Y master alloy and Mg-30Zr master alloy in an argon atmosphere. After heat preservation for 10 minutes, a magnesium alloy melt is obtained. Preheat the mold to 200°C, and in an argon atmosphere, tilt the tilting smelting equipment 75° to cast the magnesium alloy melt into the preheated mold, and air cool for 30 minutes to obtain an ingot. The ingot was placed in the tilting melting equipment again, and the tilting melting equipment was heated to 740°C. The ingot was melted again in an argon atmosphere. After heat preservation for 10 minutes, it was poured into a mold preheated to 200°C and air-cooled for 30 minutes to obtain a magnesium alloy matrix. The magnesium alloy matrix was placed in a melting furnace, and the vacuum degree in the melting furnace was set to 5×10 -2 MPa, set the temperature in the melting furnace to 680℃, melt for 20 minutes, and obtain magnesium alloy melt. Raise the temperature and superheat the melt by 60℃. When the magnesium alloy melt reaches the superheat temperature, pour it into the nozzle of the gas atomization device and use a gas flow rate of 3 m 3 / h argon gas flow impacts the molten metal, causing the magnesium alloy melt to be rapidly atomized into droplets, and then rapidly cooled into solid powder particles. After sieving, magnesium alloy powder with a particle size of 10-150 mesh was obtained. The laser power of the 3D printer was set to 400W, the scanning speed was 1000mm / s, and the scanning thickness was 0.1mm. The magnesium alloy powder was 3D printed to obtain a degradable medical 3D printed magnesium alloy cardiovascular stent.
[0042] After testing, the degradable medical 3D printed magnesium alloy cardiovascular stent of the present embodiment is composed of the following components in mass percentage: Zn 2.12wt%, Ca 0.92wt%, Y 0.38wt%, Zr 0.21wt%, impurity elements Fe≤0.08wt%, Cu≤0.005wt%, Ni≤0.002wt%, and the balance is magnesium; the degradable medical 3D printed magnesium alloy cardiovascular stent obtained in the present embodiment was subjected to a 7-day SBF simulated body fluid immersion test, and the corrosion rate was 1.12 mm / year; the degradable medical 3D printed magnesium alloy cardiovascular stent obtained in the present embodiment was subjected to a tensile test, and the yield strength was 148.5 MPa and the tensile strength was 245.3 MPa.
[0043] Example 3 Weigh 860 g magnesium ingot, 30 g zinc block, 100 g Mg-30Ca master alloy, 18 g Mg-30Y master alloy and 30 g Mg-30Zr master alloy. The weight percentage burnout rate of each element during the smelting process is Mg 5%, Zn 6%, Ca70%, Y 35%, Zr 70%. Heat the tilting smelting equipment to 750°C, and melt the weighed magnesium ingot, zinc block, Mg-30Ca master alloy, Mg-30Y master alloy and Mg-30Zr master alloy in an argon atmosphere. After heat preservation for 10 minutes, a magnesium alloy melt is obtained. Preheat the mold to 240°C, and in an argon atmosphere, tilt the tilting smelting equipment 70° to cast the magnesium alloy melt into the preheated mold, and air cool for 40 minutes to obtain an ingot. The ingot was placed in the tilting melting equipment again, and the tilting melting equipment was heated to 750°C. The ingot was melted again in an argon atmosphere. After heat preservation for 10 minutes, it was poured into a mold preheated to 240°C and air-cooled for 40 minutes to obtain a magnesium alloy matrix. The magnesium alloy matrix was placed in a melting furnace, and the vacuum degree in the melting furnace was set to 5×10 -3 MPa, set the temperature in the melting furnace to 710℃, melt for 30 minutes, and obtain magnesium alloy melt. Raise the temperature and superheat the melt to 70℃. When the magnesium alloy melt reaches the superheat temperature, pour it into the nozzle of the gas atomization device and use a gas flow rate of 4 m 3 / h argon gas flow impacts the molten metal, causing the magnesium alloy melt to be rapidly atomized into droplets, and then rapidly cooled into solid powder particles. After sieving, magnesium alloy powder with a particle size of 10-150 mesh was obtained. The laser power of the 3D printer was set to 300W, the scanning speed was 600mm / s, and the scanning thickness was 0.1mm. The magnesium alloy powder was 3D printed to obtain a degradable medical 3D printed magnesium alloy cardiovascular stent.
[0044] After testing, the degradable medical 3D printed magnesium alloy cardiovascular stent of the present embodiment is composed of the following components in mass percentage: Zn 2.88wt%, Ca 0.91wt%, Y 0.35wt%, Zr 0.28wt%, impurity elements Fe≤0.08wt%, Cu≤0.005wt%, Ni≤0.002wt%, and the balance is magnesium; the degradable medical 3D printed magnesium alloy cardiovascular stent obtained in the present embodiment was subjected to a 7-day SBF simulated body fluid immersion test, and the corrosion rate was 1.14 mm / year; the degradable medical 3D printed magnesium alloy cardiovascular stent obtained in the present embodiment was subjected to a tensile test, and the yield strength was 143.3 MPa and the tensile strength was 237.6 MPa.
[0045] Example 4 Weigh 870 g magnesium ingot, 25 g zinc block, 110 g Mg-30Ca master alloy, 15 g Mg-30Y master alloy and 20 g Mg-30Zr master alloy. The weight percentage burnout rate of each element during the smelting process is Mg 5%, Zn 6%, Ca70%, Y 35%, Zr 70%. Heat the tilting smelting equipment to 750°C, and melt the weighed magnesium ingot, zinc block, Mg-30Ca master alloy, Mg-30Y master alloy and Mg-30Zr master alloy in an argon atmosphere. After heat preservation for 10 minutes, a magnesium alloy melt is obtained. Preheat the mold to 235°C, and in an argon atmosphere, tilt the tilting smelting equipment 80° to cast the magnesium alloy melt into the preheated mold, and air cool for 30 minutes to obtain an ingot. The ingot was placed in the tilting melting equipment again, and the tilting melting equipment was heated to 750°C. The ingot was melted again in an argon atmosphere. After heat preservation for 10 minutes, it was poured into a mold preheated to 235°C and air-cooled for 30 minutes to obtain a magnesium alloy matrix. The magnesium alloy matrix was placed in a melting furnace, and the vacuum degree in the melting furnace was set to 5×10 -3 MPa, set the temperature in the melting furnace to 690℃, melt for 25 minutes, and obtain magnesium alloy melt. Raise the temperature and superheat the melt by 80℃. When the magnesium alloy melt reaches the superheat temperature, pour it into the nozzle of the gas atomization device and use a gas flow rate of 3 m 3 / h argon gas flow impacts the molten metal, causing the magnesium alloy melt to be quickly atomized into droplets, and then quickly cooled into solid powder particles. After sieving, magnesium alloy powder with a particle size of 10-150 mesh was obtained. The laser power of the 3D printer was set to 250W, the scanning speed was 800mm / s, and the scanning thickness was 0.1mm. The magnesium alloy powder was 3D printed to obtain a degradable medical 3D printed magnesium alloy cardiovascular stent.
[0046] After testing, the degradable medical 3D printed magnesium alloy cardiovascular stent of the present embodiment is composed of the following components in mass percentage: Zn 2.38wt%, Ca 0.99wt%, Y 0.31wt%, Zr 0.20wt%, impurity elements Fe≤0.08wt%, Cu≤0.005wt%, Ni≤0.002wt%, and the balance is magnesium; the degradable medical 3D printed magnesium alloy cardiovascular stent obtained in the present embodiment was subjected to a 7-day SBF simulated body fluid immersion test, and the corrosion rate was 1.07 mm / year; the degradable medical 3D printed magnesium alloy cardiovascular stent obtained in the present embodiment was subjected to a tensile test, and the yield strength was 145.6 MPa and the tensile strength was 239.5 MPa.
[0047] Example 5 Weigh 865 g magnesium ingot, 30 g zinc block, 105 g Mg-30Ca master alloy, 15 g Mg-30Y master alloy and 30 g Mg-30Zr master alloy. The weight percentage burnout rate of each element during the smelting process is Mg 5%, Zn 6%, Ca70%, Y 35%, Zr 70%. Heat the tilting smelting equipment to 730°C, and melt the weighed magnesium ingot, zinc block, Mg-30Ca master alloy, Mg-30Y master alloy and Mg-30Zr master alloy in an argon atmosphere. After heat preservation for 10 minutes, a magnesium alloy melt is obtained. Preheat the mold to 250°C, and in an argon atmosphere, tilt the tilting smelting equipment 80° to cast the magnesium alloy melt into the preheated mold, and air cool for 30 minutes to obtain an ingot. The ingot was placed in the tilting melting equipment again, and the tilting melting equipment was heated to 730°C. The ingot was melted again in an argon atmosphere. After heat preservation for 10 minutes, it was poured into a mold preheated to 250°C and air-cooled for 30 minutes to obtain a magnesium alloy matrix. The magnesium alloy matrix was placed in a melting furnace, and the vacuum degree in the melting furnace was set to 5×10 -3 MPa, set the temperature in the melting furnace to 720℃, melt for 30 minutes, and obtain magnesium alloy melt. Raise the temperature and superheat the melt by 50℃. When the magnesium alloy melt reaches the superheat temperature, pour it into the nozzle of the gas atomization device and use a gas flow rate of 2.5 m 3 / h argon gas flow impacts the molten metal, causing the magnesium alloy melt to be quickly atomized into droplets, and then quickly cooled into solid powder particles. After sieving, magnesium alloy powder with a particle size of 10-150 mesh was obtained. The laser power of the 3D printer was set to 250W, the scanning speed was 800mm / s, and the scanning thickness was 0.1mm. The magnesium alloy powder was 3D printed to obtain a degradable medical 3D printed magnesium alloy cardiovascular stent.
[0048] After testing, the degradable medical 3D printed magnesium alloy cardiovascular stent of the present embodiment is composed of the following components in mass percentage: Zn 2.76wt%, Ca 0.96wt%, Y 0.33wt%, Zr 0.24wt%, impurity elements Fe≤0.08wt%, Cu≤0.005wt%, Ni≤0.002wt%, and the balance is magnesium; the degradable medical 3D printed magnesium alloy cardiovascular stent obtained in the present embodiment was subjected to a 7-day SBF simulated body fluid immersion test, and the corrosion rate was 1.17 mm / year; the degradable medical 3D printed magnesium alloy cardiovascular stent obtained in the present embodiment was subjected to a tensile test, and the yield strength was 142.9 MPa and the tensile strength was 237.3 MPa.
[0049] Comparative Example 1 Weigh 860 g magnesium ingot, 40 g zinc block, 100 g Mg-30Ca master alloy, 20 g Mg-30Y master alloy and 25 g Mg-30Zr master alloy. The weight percentage burnout rate of each element during the smelting process is Mg 5%, Zn 6%, Ca70%, Y 35%, Zr 70%. Heat the tilting smelting equipment to 730°C, and melt the weighed magnesium ingot, zinc block, Mg-30Ca master alloy, Mg-30Y master alloy and Mg-30Zr master alloy in an argon atmosphere. After heat preservation for 10 minutes, a magnesium alloy melt is obtained. Preheat the mold to 250°C, and in an argon atmosphere, tilt the tilting smelting equipment 80° to cast the magnesium alloy melt into the preheated mold, and air cool for 30 minutes to obtain an ingot. The ingot was placed in the tilting melting equipment again, and the tilting melting equipment was heated to 730°C. The ingot was melted again in an argon atmosphere. After heat preservation for 10 minutes, it was poured into a mold preheated to 250°C and air-cooled for 30 minutes to obtain a magnesium alloy matrix. The magnesium alloy matrix was placed in a melting furnace, and the vacuum degree in the melting furnace was set to 5×10 -3 MPa, set the temperature in the melting furnace to 720℃, melt for 30 minutes, and obtain magnesium alloy melt. Raise the temperature and superheat the melt by 50℃. When the magnesium alloy melt reaches the superheat temperature, pour it into the nozzle of the gas atomization device and use a gas flow rate of 2.5 m 3 / h argon gas flow impacts the molten metal, causing the magnesium alloy melt to be quickly atomized into droplets, and then quickly cooled into solid powder particles. After sieving, magnesium alloy powder with a particle size of 10-150 mesh was obtained. The laser power of the 3D printer was set to 250W, the scanning speed was 800mm / s, and the scanning thickness was 0.1mm. The magnesium alloy powder was 3D printed to obtain a degradable medical 3D printed magnesium alloy cardiovascular stent.
[0050] After testing, the degradable medical 3D printed magnesium alloy cardiovascular stent of the present embodiment is composed of the following components in mass percentage: Zn 3.67wt%, Ca 0.93wt%, Y 0.37wt%, Zr 0.22wt%, impurity elements Fe≤0.08wt%, Cu≤0.005wt%, Ni≤0.002wt%, and the balance is magnesium; the degradable medical 3D printed magnesium alloy cardiovascular stent obtained in this comparative example was subjected to a 7-day SBF simulated body fluid immersion test, and the corrosion rate was 1.79 mm / year; the degradable medical 3D printed magnesium alloy cardiovascular stent obtained in this comparative example was subjected to a tensile test, and the yield strength was 124.7 MPa and the tensile strength was 216.7 MPa.
[0051] Comparative Example 2 Weigh 820 g magnesium ingot, 25 g zinc block, 150 g Mg-30Ca master alloy, 20 g Mg-30Y master alloy and 30 g Mg-30Zr master alloy. The weight percentage burnout rate of each element during the smelting process is Mg 5%, Zn 6%, Ca70%, Y 35%, Zr 70%. Heat the tilting smelting equipment to 730°C, and melt the weighed magnesium ingot, zinc block, Mg-30Ca master alloy, Mg-30Y master alloy and Mg-30Zr master alloy in an argon atmosphere. After heat preservation for 10 minutes, a magnesium alloy melt is obtained. Preheat the mold to 250°C, and in an argon atmosphere, tilt the tilting smelting equipment 80° to cast the magnesium alloy melt into the preheated mold, and air cool for 30 minutes to obtain an ingot. The ingot was placed in the tilting melting equipment again, and the tilting melting equipment was heated to 730°C. The ingot was melted again in an argon atmosphere. After heat preservation for 10 minutes, it was poured into a mold preheated to 250°C and air-cooled for 30 minutes to obtain a magnesium alloy matrix. The magnesium alloy matrix was placed in a melting furnace, and the vacuum degree in the melting furnace was set to 5×10 -3 MPa, set the temperature in the melting furnace to 720℃, melt for 30 minutes, and obtain magnesium alloy melt. Raise the temperature and superheat the melt by 50℃. When the magnesium alloy melt reaches the superheat temperature, pour it into the nozzle of the gas atomization device and use a gas flow rate of 2.5 m 3 / h argon gas flow impacts the molten metal, causing the magnesium alloy melt to be quickly atomized into droplets, and then quickly cooled into solid powder particles. After sieving, magnesium alloy powder with a particle size of 10-150 mesh was obtained. The laser power of the 3D printer was set to 250W, the scanning speed was 800mm / s, and the scanning thickness was 0.1mm. The magnesium alloy powder was 3D printed to obtain a degradable medical 3D printed magnesium alloy cardiovascular stent.
[0052] After testing, the degradable medical 3D printed magnesium alloy cardiovascular stent of the present embodiment is composed of the following components in mass percentage: Zn 2.46wt%, Ca 1.35wt%, Y 0.33wt%, Zr 0.26wt%, impurity elements Fe≤0.08wt%, Cu≤0.005wt%, Ni≤0.002wt%, and the balance is magnesium; the degradable medical 3D printed magnesium alloy cardiovascular stent obtained in this comparative example was subjected to a 7-day SBF simulated body fluid immersion test, and the corrosion rate was 2.05 mm / year; the degradable medical 3D printed magnesium alloy cardiovascular stent obtained in this comparative example was subjected to a tensile test, and the yield strength was 121.8 MPa and the tensile strength was 214.1 MPa.
[0053] Comparative Example 3 Weigh 850 g magnesium ingot, 25 g zinc block, 105 g Mg-30Ca master alloy, 35 g Mg-30Y master alloy and 25 g Mg-30Zr master alloy. The weight percentage burnout rate of each element during the smelting process is Mg 5%, Zn 6%, Ca70%, Y 35%, Zr 70%. Heat the tilting smelting equipment to 730°C, and melt the weighed magnesium ingot, zinc block, Mg-30Ca master alloy, Mg-30Y master alloy and Mg-30Zr master alloy in an argon atmosphere. After heat preservation for 10 minutes, a magnesium alloy melt is obtained. Preheat the mold to 250°C, and in an argon atmosphere, tilt the tilting smelting equipment 80° to cast the magnesium alloy melt into the preheated mold, and air cool for 30 minutes to obtain an ingot. The ingot was placed in the tilting melting equipment again, and the tilting melting equipment was heated to 730°C. The ingot was melted again in an argon atmosphere. After heat preservation for 10 minutes, it was poured into a mold preheated to 250°C and air-cooled for 30 minutes to obtain a magnesium alloy matrix. The magnesium alloy matrix was placed in a melting furnace, and the vacuum degree in the melting furnace was set to 5×10 -3 MPa, set the temperature in the melting furnace to 720℃, melt for 30 minutes, and obtain magnesium alloy melt. Raise the temperature and superheat the melt by 50℃. When the magnesium alloy melt reaches the superheat temperature, pour it into the nozzle of the gas atomization device and use a gas flow rate of 2.5 m 3 / h argon gas flow impacts the molten metal, causing the magnesium alloy melt to be quickly atomized into droplets, and then quickly cooled into solid powder particles. After sieving, magnesium alloy powder with a particle size of 10-150 mesh was obtained. The laser power of the 3D printer was set to 250W, the scanning speed was 800mm / s, and the scanning thickness was 0.1mm. The magnesium alloy powder was 3D printed to obtain a degradable medical 3D printed magnesium alloy cardiovascular stent.
[0054] After testing, the degradable medical 3D printed magnesium alloy cardiovascular stent of the present embodiment is composed of the following components in mass percentage: Zn 2.58wt%, Ca 0.95wt%, Y 0.69wt%, Zr 0.24wt%, impurity elements Fe≤0.08wt%, Cu≤0.005wt%, Ni≤0.002wt%, and the balance is magnesium; the degradable medical 3D printed magnesium alloy cardiovascular stent obtained in this comparative example was subjected to a 7-day SBF simulated body fluid immersion test, and the corrosion rate was 1.60 mm / year; the degradable medical 3D printed magnesium alloy cardiovascular stent obtained in this comparative example was subjected to a tensile test, and the yield strength was 117.2 MPa and the tensile strength was 210.2 MPa.
[0055] Comparative Example 4 Weigh 895 g magnesium ingot, 25 g zinc block, 100 g Mg-30Ca master alloy, 15 g Mg-30Y master alloy and 5 g Mg-30Zr master alloy. The weight percentage burnout rate of each element during the smelting process is Mg 5%, Zn 6%, Ca 70%, Y 35%, and Zr 70%. Heat the tilting smelting equipment to 730°C, and melt the weighed magnesium ingot, zinc block, Mg-30Ca master alloy, Mg-30Y master alloy and Mg-30Zr master alloy in an argon atmosphere. After heat preservation for 10 minutes, a magnesium alloy melt is obtained. Preheat the mold to 250°C, and in an argon atmosphere, tilt the tilting smelting equipment 80° to cast the magnesium alloy melt into the preheated mold, and air cool for 30 minutes to obtain an ingot. The ingot was placed in the tilting melting equipment again, and the tilting melting equipment was heated to 730°C. The ingot was melted again in an argon atmosphere. After heat preservation for 10 minutes, it was poured into a mold preheated to 250°C and air-cooled for 30 minutes to obtain a magnesium alloy matrix. The magnesium alloy matrix was placed in a melting furnace, and the vacuum degree in the melting furnace was set to 5×10 -3 MPa, set the temperature in the melting furnace to 720℃, melt for 30 minutes, and obtain magnesium alloy melt. Raise the temperature and superheat the melt by 50℃. When the magnesium alloy melt reaches the superheat temperature, pour it into the nozzle of the gas atomization device and use a gas flow rate of 2.5 m 3 / h argon gas flow impacts the molten metal, causing the magnesium alloy melt to be quickly atomized into droplets, and then quickly cooled into solid powder particles. After sieving, magnesium alloy powder with a particle size of 10-150 mesh was obtained. The laser power of the 3D printer was set to 250W, the scanning speed was 800mm / s, and the scanning thickness was 0.1mm. The magnesium alloy powder was 3D printed to obtain a degradable medical 3D printed magnesium alloy cardiovascular stent.
[0056] After testing, the degradable medical 3D printed magnesium alloy cardiovascular stent of the present embodiment is composed of the following components in mass percentage: Zn 2.35wt%, Ca 0.92wt%, Y 0.34wt%, Zr 0.05wt%, impurity elements Fe≤0.08wt%, Cu≤0.005wt%, Ni≤0.002wt%, and the balance is magnesium; the degradable medical 3D printed magnesium alloy cardiovascular stent obtained in this comparative example was subjected to a 7-day SBF simulated body fluid immersion test, and the corrosion rate was 1.45 mm / year; the degradable medical 3D printed magnesium alloy cardiovascular stent obtained in this comparative example was subjected to a tensile test, and the yield strength was 112.1 MPa and the tensile strength was 203.2 MPa.
[0057] Comparative Example 5 Weigh 870 g magnesium ingot, 25 g zinc block, 100 g Mg-30Ca master alloy, 20 g Mg-30Y master alloy and 25 g Mg-30Zr master alloy. The weight percentage burnout rate of each element during the smelting process is Mg 5%, Zn 6%, Ca70%, Y 35%, Zr 70%. Heat the tilting smelting equipment to 730°C, and melt the weighed magnesium ingot, zinc block, Mg-30Ca master alloy, Mg-30Y master alloy and Mg-30Zr master alloy in an argon atmosphere. After heat preservation for 10 minutes, a magnesium alloy melt is obtained. Preheat the mold to 250°C, and in an argon atmosphere, tilt the tilting smelting equipment 80° to cast the magnesium alloy melt into the preheated mold, and air cool for 30 minutes to obtain an ingot. The ingot was placed in the tilting melting equipment again, and the tilting melting equipment was heated to 730°C. The ingot was melted again in an argon atmosphere. After heat preservation for 10 minutes, it was poured into a mold preheated to 250°C and air-cooled for 30 minutes to obtain a magnesium alloy matrix. The magnesium alloy matrix was placed in a melting furnace, and the vacuum degree in the melting furnace was set to 5×10 -3 MPa, set the temperature in the melting furnace to 720℃, melt for 30 minutes, and obtain magnesium alloy melt. Raise the temperature and superheat the melt by 50℃. When the magnesium alloy melt reaches the superheat temperature, pour it into the nozzle of the gas atomization device and use a gas flow rate of 2.5 m 3 / h argon gas flow impacts the molten metal, causing the magnesium alloy melt to be quickly atomized into droplets and quickly cooled into solid powder particles. After sieving, magnesium alloy powder with a particle size of 10-150 mesh was obtained. The laser power of the 3D printer was set to 100W, the scanning speed was 800mm / s, and the scanning thickness was 0.1mm. The magnesium alloy powder was 3D printed to obtain a degradable medical 3D printed magnesium alloy cardiovascular stent.
[0058] After testing, the degradable medical 3D printed magnesium alloy cardiovascular stent of the present embodiment is composed of the following components in mass percentage: Zn 2.37wt%, Ca 0.91wt%, Y 0.37wt%, Zr 0.23wt%, impurity elements Fe≤0.08wt%, Cu≤0.005wt%, Ni≤0.002wt%, and the balance is magnesium; the degradable medical 3D printed magnesium alloy cardiovascular stent obtained in this comparative example was subjected to a 7-day SBF simulated body fluid immersion test, and the corrosion rate was 1.59 mm / year; the degradable medical 3D printed magnesium alloy cardiovascular stent obtained in this comparative example was subjected to a tensile test, and the yield strength was 102.4 MPa and the tensile strength was 195.4 MPa.
[0059] The degradable medical 3D printed magnesium alloy cardiovascular stents prepared in Examples 1 to 5 of the present invention and Comparative Examples 1 to 5 were subjected to a 7-day SBF simulated body fluid immersion test. The test data show that the corrosion rate of the degradable medical 3D printed magnesium alloy cardiovascular stent prepared by the present invention in the SBF simulated body fluid immersion test is 1.00 to 1.20 mm / year, which can ensure that the stent can maintain relatively high mechanical properties in the body, while being able to moderately degrade and promote the healing and regeneration of blood vessels. The high content of alloying elements in Comparative Examples 1-3 will lead to alloy precipitation, the appearance of more second phase particles, which act as the cathode of corrosion and form a micro-battery effect with the magnesium matrix, thereby accelerating local corrosion. In Comparative Example 4, the Zr content is low, the grains of the magnesium alloy are coarse, and there are more exposed grain boundaries, which are easy to become the origin of corrosion, resulting in aggravated local corrosion. In Comparative Example 5, the laser power is too low, the metal powder is not completely melted, and spheroidization, cracks, and even delamination will occur. The surface of the stent becomes very rough, making it more susceptible to erosion in a corrosive environment. It can be seen that the degradable medical 3D printed magnesium alloy cardiovascular stent prepared by the preparation method provided by the present invention has better corrosion resistance.
[0060] The degradable medical 3D printed magnesium alloy cardiovascular stent prepared in this comparative example is subjected to a tensile test. The test data show that the yield strength of the degradable medical 3D printed magnesium alloy cardiovascular stent prepared by the present invention is 140~150MPa, and the tensile strength is 230~250MPa. The microstructure of the alloy is optimized and the mechanical properties are improved by a specific magnesium alloy element ratio and specific preparation process parameters. However, the excessive content of Zn or Ca in comparative examples 1~2 causes the magnesium alloy to form larger grains during the solidification process. Large grains are prone to stress concentration when loaded, resulting in a decrease in the mechanical properties of the magnesium alloy. Excessive rare earth element content in comparative example 3 deteriorates the processing properties of the magnesium alloy, thereby reducing the yield strength and ultimate tensile strength of the magnesium alloy. In comparative example 4, the insufficient Zr content weakens the solid solution strengthening effect of Zr in the magnesium alloy, resulting in a decrease in the overall tensile strength of the alloy. In addition, zirconium can effectively inhibit the growth of grains in magnesium alloys. If the zirconium content is too low, the grain refinement effect will be weakened, resulting in a larger grain size of the alloy, thereby reducing the mechanical properties. In Comparative Example 5, the laser power is too low, resulting in the failure of the magnesium alloy to completely melt during the printing process, resulting in a decrease in the density of the magnesium alloy and an increase in internal defects (such as pores and cracks), which significantly reduces the overall mechanical properties of the alloy. It can be seen that the degradable medical 3D printed magnesium alloy cardiovascular stent prepared by the preparation method of the degradable medical 3D printed magnesium alloy cardiovascular stent provided by the present invention has better mechanical properties.
[0061] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A degradable medical 3D printed magnesium alloy cardiovascular stent, characterized in that: The magnesium alloy cardiovascular stent is composed of the following components in percentage by mass: Zinc 2.0~3.0wt%; Calcium 0.9~1.0wt%; Yttrium 0.3~0.4wt%; Zirconium 0.2~0.3wt%; The balance is magnesium and unavoidable impurities; The unavoidable impurities consist of the following components in percentage by mass: Iron ≤ 0.08wt%; Copper ≤ 0.005wt%; Nickel ≤ 0.002wt%.
2. A method for preparing a degradable medical 3D printed magnesium alloy cardiovascular stent as claimed in claim 1, characterized in that: The following steps are involved: (1) According to the elemental composition of the degradable medical 3D printed magnesium alloy cardiovascular stent, weigh the magnesium ingot, zinc block, Mg-30Ca master alloy, Mg-30Y master alloy and Mg-30Zr master alloy; (2) heating the smelting equipment, and smelting the magnesium ingot, zinc block, Mg-30Ca master alloy, Mg-30Y master alloy and Mg-30Zr master alloy under a protective atmosphere, and obtaining a magnesium alloy melt after heat preservation treatment; (3) Preheating the mold, pouring the magnesium alloy melt into the preheated mold under a protective atmosphere, and cooling to obtain an ingot; (4) remelting the ingot, keeping it warm, pouring it into a preheated mold, and cooling it to obtain a magnesium alloy base material; (5) melting the magnesium alloy base material to obtain a magnesium alloy melt; (6) Raising the temperature to superheat the melt, transferring it to a gas atomization device, cooling it into solid powder particles, and sieving it to obtain magnesium alloy powder; (7) The magnesium alloy powder is 3D printed to obtain a biodegradable medical 3D printed magnesium alloy cardiovascular stent.
3. The method for preparing a degradable medical 3D printed magnesium alloy cardiovascular stent according to claim 2, characterized in that: The protective atmosphere is argon gas.
4. The method for preparing a degradable medical 3D printed magnesium alloy cardiovascular stent according to claim 2, characterized in that: In the step (2), the temperature of the smelting equipment is raised to 720-750° C., and the insulation treatment time is 10 minutes.
5. The method for preparing a degradable medical 3D printed magnesium alloy cardiovascular stent according to claim 2, characterized in that: In the step (3), the mold is preheated to 200-250° C. and the cooling time is 20-40 minutes.
6. The method for preparing a degradable medical 3D printed magnesium alloy cardiovascular stent according to claim 2, characterized in that: In the step (4), the smelting temperature is 720-750° C. and the holding time is 10 minutes.
7. The method for preparing a degradable medical 3D printed magnesium alloy cardiovascular stent according to claim 2, characterized in that: In the step (4), the mold is preheated to 200-250° C. and the cooling time is 20-40 minutes.
8. The method for preparing a degradable medical 3D printed magnesium alloy cardiovascular stent according to claim 2, characterized in that: In the step (5), the vacuum degree in the furnace during smelting is 10 -2 ~10 -3 MPa, the smelting temperature is 680~720℃, and the smelting time is 20~30 minutes.
9. The method for preparing a degradable medical 3D printed magnesium alloy cardiovascular stent according to claim 2, characterized in that: In step (6), the melt is superheated to 50-100°C, the high-speed gas in the atomization device is argon, and the gas flow rate is 2-4 m 3 / h, and the particle size distribution after screening is 10~150 mesh.
10. The method for preparing a degradable medical 3D printed magnesium alloy cardiovascular stent according to claim 2, characterized in that: In step (7), the process parameters of 3D printing are: laser power 200-400 W, scanning speed 600-1000 mm / s, and scanning layer thickness 0.1 mm.
Citation Information
Patent Citations
Medical degradable multi-element Mg-Zn-Y-Ca-Zr alloy with high strength and toughness and corrosion resistance, and preparation method thereof
CN107236886A
Preparing method, material and application of medical magnesium alloy material used for 3D printing
CN107245618A
An implant comprising magnesium alloy and a method for preparing thereof
US20240050623A1